2016
DOI: 10.3892/mmr.2016.4933
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200b inhibits epithelial-mesenchymal transition and migration of cervical cancer cells by directly targeting RhoE

Abstract: Previous studies have identified microRNA-200b (miR-200b) as a powerful regulator of epithelial-mesenchymal transition (EMT) via the control of gene expression. EMT is a critical event that is associated with the initiation of malignant tumor metastasis. A lack of E-cadherin expression and overexpression of vimentin are hallmarks of EMT. It is well‑known that RhoE, which is associated with regulation of the actin cytoskeleton and migration via alterations in cell motility, regulates the expression of E-cadheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…It is well acknowledged that microRNA is closely related to pathological process of several kinds of cancers such as cervical cancer (17,18). Importantly some studies have found that specific microRNA can regulate EMT of tumor cells (25)(26)(27)(28)(29)(30)(31)(32). In the present study, we found that miR-106b and its target protein DAB2 play significantly important regulatory roles in EMT process of cervical cancer cell lines SiHa and HeLa.…”
Section: Discussionsupporting
confidence: 51%
“…It is well acknowledged that microRNA is closely related to pathological process of several kinds of cancers such as cervical cancer (17,18). Importantly some studies have found that specific microRNA can regulate EMT of tumor cells (25)(26)(27)(28)(29)(30)(31)(32). In the present study, we found that miR-106b and its target protein DAB2 play significantly important regulatory roles in EMT process of cervical cancer cell lines SiHa and HeLa.…”
Section: Discussionsupporting
confidence: 51%
“…A number of miRNAs have been demonstrated to regulate EMT, thereby playing a role in the regulation of invasion and metastasis. miR-200 family, a known family of tumor suppressor miRNAs with well characterized role in EMT of cancer cells [202], has been implicated in EMT of OC cells [203, 204] as well as CC cells [205, 206]. Another member of this family, miR-429, has also been shown to reverse EMT [207].…”
Section: Biological Significance Of Mirnas In Gynecologic Cancersmentioning
confidence: 99%
“…miR-200a has been reported overexpressed in serum [71] whereas miR-200b has a controversial reported expression, while Cheng et al [119] and Cheng et al reported [120] a down-regulation, Zeng et al reported an up-regulation [121]. miR-200b mimic reduces migration and it seems that its overexpression inhibits EMT because E -cadherin is augmented and vimentin a matrix metalloproteinase-9 is decreased [119] by targeting RhoE directly which binds Guanosine-5’-triphosphate (GTP) but has no GTPase activity, and appears to act as a negative regulator of cytoskeletal organization leading to loss of adhesion, favoring migration and invasion [120]. On the other hand, miR-200b inhibition inhibits cell migration, invasion and tumor growth by targeting Forkhead Box G1 (FoxG1) a transcriptional repressor [121].…”
Section: Mir-200 Family Participates In Cervical Cancermentioning
confidence: 99%